Investigating the big five factors on psychological well- being among retirees in Akure south local government area of Ondo - State (2012)
The survey study examined the influence of the big five factors (extraversion, agreeableness, neuroticism, conscientiousness and openness) on the psychological well-being of250 retirees in Akure, Ondo state, Nigeria. Ex-post facto design was employed using structured questionnaires. Findings indicated that the predictor variables jointly predicted psychological well-being of retirees F (5,238) = 4.215, p <.001. Conscientiousness and openness as stated in the first hypothesis independently predicted psychological well-being of retirees (P = - 0.322, t = - 4.068, p<.001 and ft = - 0.210, t = - 3.062, p<.01) respectively. The second hypothesis which tested marital status difference in psychological well-being was confirmed with divorced retirees experienced negative psychological well-being than widow(er), single and married F (3, 240) = 4.74, p<.01). Finally, gender difference on dimension of psychological well-being was confirmed with males scoring higher on somatic symptoms than females t (242) = 2.64, p<.01. These findings were discussed in line with existing literature and recommendations made